INTELLECTUAL PROPERTY, DESIGN AND THE INTERNET - Rakhimzhanova G.B. Рахимжанова Г.Б. (Рroblems of engineering and professional education, 2023)
The article reveals the risks of designers’ work in terms of moderntechnology. The following problems are considered: the problem of protection ofcopyright and patent rights in connection with the development of the Internet; the problem of international regulation in the field of intellectual property rights,where the use of someone else’s intellectual property by foreigners in other countries is practically impossible to prevent and stop; the problem of the economic interest of large companies to use somebody else’s unpaid labor to make a profit without compensation to authors of works or industrial designs.